Luxembourg : Selected Issues and Statistical Appendix. (IMF Staff Country Reports; Country Report, 2000)
Luxembourg's impressive growth performance has been accompanied by regional specialization of production, high labor mobility, export-propelled growth, and the dominance of regional growth fluctuations. Luxembourg's public pension system faces the challenges of population aging and Luxembourg's small, open, and highly specialized economy. Luxembourg's labor market performance holds a seeming paradox, favorable labor market outcomes are coupled with rigid labor market institutions. The supervision of cross-border financial activities raises the difficult challenge of obtaining a complete, consolidated view of the operations of international banking institutions.